Ethno-Cultural Education in the Republic of Buryatia: Problems and Prospects of Solution - Svetlana A. Kharitonova (Publishing house "Sreda", 2020)
The article is devoted to the consireation of problems arising in the implementation of ethno-cultural education. The purpose of article is to consider the main problems of modern ethno-cultural education in the Republic of Buryatia and suggest ways to solve them. The methods of the article are based on a theoretical analysis of research on this issue and monitoring data on ethno-cultural education in the Republic of Buryatia. As a result of this work, the main existing problems of ethno-cultural education in Buryatia are highlighted. It is concluded that modern ethno-cultural education should be aimed at the formation of multi-ethnic cultural competence of the individual and be implemented at all levels of education. State authorities, public and interested organizations whose activities are aimed at the development of multi-ethnic culture of modern youth should be involved in solving the problems that arise in the implementation of ethno-cultural education.